DESAIN ALAT CABUT SINGKONG SISTEM SLING OTOMATIS UNTUK DIGUNAKAN PADA PROSES PANEN - Susanti Sundari; Aam Wahyu Pratama; Ghapur Hidayat (Industrika : Jurnal Ilmiah Teknik Industri, 2022)
The design of the cassava extractor in this study differs from the existing concept where the automatic cassava extractor uses only a small amount of human power. The purpose of this study was to design a cassava extractor using an automatic sling system to facilitate farmers in the cassava harvesting process, thereby reducing the level of injury or pain in the farmers' backs and shoulders in the long term. This research is an applied research that uses the facto exposure method to solve practical problems in everyday life. The result of this research is the design of the cassava extractor using an automatic system which is an improvement from the concept that has been made, has differences and advantages compared to the previous concept because it uses little human power, namely when wrapping the rope at the base of the cassava stem and pressing the control button. hoist crane, this tool is more flexible, easy to carry anywhere, more practical because its use just presses the up/down button on the automatic sling. In addition, this cassava extractor is more effective where with a maximum lifting capacity of 500 kg and through an intermediary sling that has been tested by SNI. This tool is able to lift more than one cassava stick at the same time for 20 seconds. Keywords: Automatic, cassava extractor, design